Age related metabolic modifications in the migraine brain. (July 2019) - Lisicki, Marco; D'Ostilio, Kevin; Coppola, Gianluca; Parisi, Vincenzo; de Noordhout, Alain Maertens; Magis, Delphine; Schoenen, Jean; Scholtes, Felix; Versijpt, Jan
Purpose: The aim of this study was to evaluate the possibility that migraine patients exhibit specific age-related metabolic changes in the brain, which occur regardless of disease duration or the frequency of attacks. Methods: We analysed the relation between brain glucose ( 18 F-fluorodeoxyglucose) uptake and age in healthy volunteers (n = 20) and episodic migraine patients (n = 19). In the latter, we additionally compared the correlation between 18 F-fluorodeoxyglucose uptake and disease duration and monthly migraine days. Results: In contrast to controls, in migraine patients advancing age was positively correlated to increased metabolism in the brainstem (especially the posterior pons), hippocampus, fusiform gyrus and parahippocampus. Conversely, no significant correlations between cerebral metabolism and disease duration or migraine days were observed. Conclusions: Findings of this cross-sectional study show that episodic migraine patients exhibit specific metabolic brain modifications while ageing. As such, age is correlated with metabolic changes in key regions of the brain previously associated with migraine's pathophysiology to a better extent than disease duration or the number of monthly migraine days. More than the repeated headache attacks, the continuous interaction with the environment seemingly models the brain of migraine sufferers in an adaptive manner. A positive control (e.g. chronic pain) is missing in this study and therefore findings cannot be proven to be migraine-specific.